The Importance of Decarbonylation Mechanisms in the Atomic Layer Deposition of High‐Quality Ru Films by Zero‐Oxidation State Ru(DMBD)(CO)3. Issue 9 (5th January 2022) - Schneider, Joel R.; de Paula, Camila; Lewis, Jacqueline; Woodruff, Jacob; Raiford, James A.; Bent, Stacey F.
Abstract: Achieving facile nucleation of noble metal films through atomic layer deposition (ALD) is extremely challenging. To this end, η 4 ‐2, 3‐dimethylbutadiene ruthenium (0) tricarbonyl (Ru(DMBD)(CO)3 ), a zero‐valent complex, has recently been reported to achieve good nucleation by ALD at relatively low temperatures and mild reaction conditions. The authors study the growth mechanism of this precursor by in situ quartz‐crystal microbalance and quadrupole mass spectrometry during Ru ALD, complemented by ex situ film characterization and kinetic modeling. These studies reveal that Ru(DMBD)(CO)3 produces high‐quality Ru films with excellent nucleation properties. This results in smooth, coalesced films even at low film thicknesses, all important traits for device applications. However, Ru deposition follows a kinetically limited decarbonylation reaction scheme, akin to typical chemical vapor deposition processes, with a strong dependence on both temperature and reaction timescale. The non‐self‐limiting nature of the kinetically driven mechanism presents both challenges for ALD implementation and opportunities for process tuning. By surveying reports of similar precursors, it is suggested that the findings can be generalized to the broader class of zero‐oxidation state carbonyl‐based precursors used in thermal ALD, with insight into the design of effective saturation studies. Abstract : A mechanistic investigation complemented by kinetic modeling of ruthenium atomic layer deposition by a zero‐valent carbonyl‐based precursor reveals the importance of spontaneous decarbonylation in growth. This results in high‐quality Ru films with excellent nucleation properties at relatively low temperatures with no counter‐reactant. The reaction pathway causes both temperature and timescale to be critical parameters for controlling growth behavior.